Domains in Ferroic Crystals and Thin Films - Tagantsev, Alexander K.; Cross, L. Eric.; Fousek, Jan.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Domains in Ferroic Crystals and Thin Films presents experimental findings and theoretical understanding of ferroic (non-magnetic) domains developed during the past 60 years. It addresses the situation by looking specifically at bulk crystals and thin films, with a particular focus on recently-developed microelectronic applications and methods for observation of domains with techniques such as scanning force microscopy, polarized light microscopy, scanning optical microscopy, electron microscopy, and surface decorating techniques. Domains in Ferroic Crystals and Thin Films covers a large area of material properties and effects connected with static and dynamic properties of domains, which are extremely relevant to materials referred to as ferroics. In most solid state physics books, one large group of ferroics is customarily covered: those in which magnetic properties play a dominant role. Numerous books are specifically devoted to magnetic ferroics and cover a wide spectrum of magnetic domain phenomena. In contrast, Domains in Ferroic Crystals and Thin Films concentrates on domain-related phenomena in nonmagnetic ferroics. These materials are still inadequately represented in solid state physics, and this volume fills that need.
A Preview of Concepts and Phenomena -- Fundamentals of Ferroic Domain Structures -- Ferroic Materials -- Methods for Observation of Domains -- Static Domain Patterns -- Domain Walls at Rest -- Switching Properties: Basic Methods and Characteristics -- Switching Phenomena and Small-Signal Response -- Ferroelectric Thin Films.
Keywords: Physics; Magnetism; Surfaces (Physics).; Physics; Magnetism, Magnetic Materials; Surfaces and Interfaces, Thin Films; Characterization and Evaluation of Materials